Beyond the Diffusion of Residential Solar Photovoltaic Systems at Scale: Allegorising the Battery Energy Storage Adoption Behaviour - Alipour, Mohammad; Stewart, Rodney A.; Sahin, Oz (Energies (Basel), 2021)
Understanding the residential adoption decision of battery energy storage systems (BESSs) is central to the implementation of successful intervention policies. However, when the residential solar photovoltaics (PV) becomes a widely accepted technology across a society, accurately modelling the behaviour shows a higher degree of complexity. In this vein, the uptake pathway of BESS and PV coupled with BESS (PV–BESS) would predictably exhibit similar attitudinal traits to that of PV consumption. This notion implies that the antecedent PV decision can be regarded as the past behaviour of the BESS adopter by creating attitudinal implications. The PV use status also yields a higher degree of heterogeneity through the emergence of four new household groups and the inherent imbalances in the involvement of the interwoven financial, technical, sociodemographic, and psychological predictors. This perspective employs the Reasoned Action Approach (RAA) to allegorise a decision-making model of BESS and PV–BESS adoption behaviour in a mature PV market (Australia). It argues that the particularised background factors will likely shape the individual’s attitudes and perceived norms for intention, and showcases affordability and the use of PV as the two control components that dictate the final decision.